Emblems and taxonomies: catechizing Genesis 2:19 with William Jones of Nayland and Sarah Trimmer - Ney, David (Pro ecclesia, 2023)
Many Early Modern Christians believed they could participate in the fulfillment of Adam's divine mandate to name the beasts. While some took an emblematic approach to this task, others embraced a taxonomic modality. The emblematic and taxonomic modes of naming can be distinguished through the study of two late-eighteenth-century children's catechisms, William Jones of Nayland's The Book of Nature and Sarah Trimmer's An Easy Introduction to the Knowledge of Nature. These catechisms confirm that the emblematic and taxonomic responses to Adam's mandate do not merely constitute different interpretations of Genesis 2:19. They constitute different understandings of the nature of catechesis and the identity of the Old Testament itself.